2023
DOI: 10.1247/csf.22068
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of functional tight junctions with individual claudin subtypes in epithelial cells

Abstract: The claudin family of membrane proteins is responsible for the backbone structure and function of tight junctions (TJs), which regulate the paracellular permeability of epithelia.It is thought that each claudin subtype has its own unique function and the combination of expressed subtypes determines the permeability property of each epithelium. However, many issues remain unsolved in regard to claudin functions, including the detailed functional differences between claudin subtypes and the effect of the combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Other factors that could influence Cldn4 polymerization are the different N-or C-terminal tags used in the studies and the species origin of the protein. The importance of all of these factors is especially evident when comparing our data to a recent study by Furuse et al (41). In the same qKO cell line, they find that Cldn4, which did not create a barrier in our experiments, makes TJ strands and introduces a strong barrier against solutes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Other factors that could influence Cldn4 polymerization are the different N-or C-terminal tags used in the studies and the species origin of the protein. The importance of all of these factors is especially evident when comparing our data to a recent study by Furuse et al (41). In the same qKO cell line, they find that Cldn4, which did not create a barrier in our experiments, makes TJ strands and introduces a strong barrier against solutes.…”
Section: Discussionsupporting
confidence: 74%
“…Due to the absence of TJ strands, small molecules and electrolytes can easily permeate between qKO cells (38). However, it has been shown that reconstitution of barrier Cldns like Cldn3 can rescue these barrier deficiencies (36, 41). As done in these past studies, we measured the permeability of a small fluorescent tracer molecule (fluorescein, 332 D) [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Others studies concluded that Cldn4 might act as a paracellular channel, either on its own [28,37] or in combination with Cldn8 [29]. In contrast, barrier-forming properties of dog Cldn4 were demonstrated by Furuse et al [38], who reported TER values of up to 4000 Ω•cm 2 when overexpressing dog Cldn4 in claudin quin KO cells. Average TER values of about 2500 Ω•cm 2 were obtained in our experiments with claudin quin KO cells expressing mouse claudin-4, whereas the TER was very low in claudin quin KO cells expressing mouse claudin-8 (averaging about 20 Ω•cm 2 ; for baseline values, see Supplemental Table S1; for an example, see Supplemental Figure S1).…”
Section: Discussionmentioning
confidence: 96%
“…The barrier characteristics of a given tissue and a given CLDN seem to be reliant on the combination of the CLDNs that are expressed and on the manner in which they copolymerize [17]. Some CLDNs exert their function via interaction with other CLDNs, e.g., CLDN23, which functions via heteromeric cis and heterotypic trans interactions with CLDN3 and CLDN4 [18], while others function independently, as in the case of channelforming CLDNs −2, 10a, 10b, and −15 [19].…”
Section: Physiological Functions Of Claudinsmentioning
confidence: 99%